Quality improvement in a multi-cavity injection moulding process using response surface methodology - Toh, H. T. (2021)
Multi-cavity injection moulding process is challenging due to increasing complexity in design and higher precision requirement. Quality defects need to be addressed effectively and systematically. This paper reports an investigation based on a case study company producing consumable injection moulded parts for medical application. The current process suffers high reject rate due to excessive warpage and gate flash where the company lose about 17% of daily production. This has significantly effected the company’s productivity. The objective of this study is to minimize warpage and gate flash of the injected moulded polyvinyl chloride (PVC) parts. Significant process parameters contributing to both warpage and gate flash defects are identified. The study also attempted to search for an optimum setting such that it could be used as a guide to concurrently improve the warpage and gate flash. A fractional factorial design and Response Surface Methodology (RSM) techniques were used. An optimum parameter setting is proposed through an overlaid contour plot that combine the two responses. The recommended feasible setting leading to an optimum performance are −1.6 for holding pressure and 0.6 for mould temperature (coded values). Practical validation indicates a significant reduction in rejection rate. This study shoud be further extended to refine the proposed regression model.